DESIGN OF A DISSOLVED AIR FLOAT (DAF) IN THE TREATMENT OF WASTE WATER A TEXTILE - Salas Colotta, G. (2004)
We presented the design of a dissolved air flotation system (DAF) to separate coagulated solids (dye) in the wastewater of a textile plant. The obtained yields of removal of suspended solids (SS) they are 82%. The size of the float to treat 35 m3/h of residual water of a textile is 5,7 m.